2015
DOI: 10.1002/humu.22816
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions ofELP4Are Associated with Language Impairment, Autism Spectrum Disorder, and Mental Retardation

Abstract: Copy-number variations (CNVs) are important in the aetiology of neurodevelopmental disorders and show broad phenotypic manifestations. We compared the presence of small CNVs disrupting the ELP4-PAX6 locus in 4,092 UK individuals with a range of neurodevelopmental conditions, clinically referred for array comparative genomic hybridization, with WTCCC controls (n = 4,783). The phenotypic analysis was then extended using the DECIPHER database. We followed up association using an autism patient cohort (n = 3,143) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Finally, this study should be considered in the broader context of the requirement for the six-subunit Elongator complex in the CNS. Variants in the ELP2 gene are associated with neurodevelopmental (including intellectual) disability (Cohen et al, 2015; Franic et al, 2015) while ELP3 variants are associated with ALS (Simpson et al, 2009; Kwee et al, 2012), and loss of ELP4 can cause Rolandic epilepsy syndrome and intellectual disability (Strug et al, 2009; Nguyen et al, 2010; Gkampeta et al, 2014; Reinthaler et al, 2014; van Blitterswijk et al, 2014; Addis et al, 2015). This study adds to the growing understanding of the critical function for the Elongator complex in the CNS by revealing the repercussions of Ikbkap loss in the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study should be considered in the broader context of the requirement for the six-subunit Elongator complex in the CNS. Variants in the ELP2 gene are associated with neurodevelopmental (including intellectual) disability (Cohen et al, 2015; Franic et al, 2015) while ELP3 variants are associated with ALS (Simpson et al, 2009; Kwee et al, 2012), and loss of ELP4 can cause Rolandic epilepsy syndrome and intellectual disability (Strug et al, 2009; Nguyen et al, 2010; Gkampeta et al, 2014; Reinthaler et al, 2014; van Blitterswijk et al, 2014; Addis et al, 2015). This study adds to the growing understanding of the critical function for the Elongator complex in the CNS by revealing the repercussions of Ikbkap loss in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that tRNA from FD patients contains reduced levels of the modified wobble nucleoside mcm 5 s 2 U 34 (Lin et al, 2013; Karlsborn et al, 2014a; Yoshida et al, 2015), lending support to a direct function of IKAP in translation. Interestingly, three other Elongator subunits, ELP2 to ELP4 , have each been associated with CNS disorders (Nguyen et al, 2010): ELP2 and ELP4 have been implicated in intellectual development disorders (Cohen et al, 2015; Franic et al, 2015; Addis et al, 2015) and epilepsy (Gkampeta et al, 2014; Reinthaler et al, 2014; Strug et al, 2009), and ELP3 with amyotrophic lateral sclerosis (Simpson et al, 2009; Kwee et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The Elongator complex, a histone acetyltransferase complex that associates directly with RNA polymerase II during transcriptional elongation, is required for proper generation of IPs in the developing cerebral cortex. Elongator is a macromolecular complex (Elp1-Elp6) expressed in the developing nervous system (Creppe et al, 2009) and mutations that decrease its function are associated with neurodegenerative diseases, such as ALS and familial dysautonomia (Anderson et al, 2001;Slaugenhaupt et al, 2001;Simpson et al, 2009) as well as intellectual disability and autism (Addis et al, 2015;Cohen et al, 2015). A role for this complex in the control of projection neuron migration and differentiation was through its acetylation of ␣-tubulin (Creppe et al, 2009).…”
Section: Timing Of Neurogenesis and Its Indirect Regulation Via Intermentioning
confidence: 99%
“…The Elongator complex has also been shown to be required in the nucleus for normal transcript elongation [18, 19] and to negatively regulate exocytosis in yeast and C.elegans , and is required for vesicle trafficking, cytoskeleton stability and dynamics [2026], and neuronal survival [2729]. Interestingly, IKAP is just one of six subunits of the Elongator complex and recently it has become clear that several of the other Elongator genes are also associated with neurological disorders: ELP3 with amyotrophic lateral sclerosis, ELP2 and ELP4 with intellectual disability and ELP4 with Rolandic epilepsy [3036]. …”
Section: Introductionmentioning
confidence: 99%